Spatial use of marine resources in a rural village: A case study from Qoma, Fiji - Kitolelei, Salanieta; Lowry, John H.; Qaqara, Nemillie; Ryle, Jacqueline; Veitayaki, Joeli; Piovano, Susanna (Frontiers in Marine Science, 2022)
The aim of this case study was to investigate and document Indigenous and Traditional Knowledge of marine resources in Qoma, a rural fishing village in Fiji. Using a sex-age lens, our research combines theory and methods from Participatory Geographic Information Systems and ethnography. We document how men and women use geographic space in their traditional fishing grounds showing that generally men travel significantly farther to harvest marine resources than women. Targeted marine resources and knowledge of those resources differ between men and women, reflecting the traditional roles of men and women within Indigenous Fijian (iTaukei) culture. Fishermen and fisherwomen of 60+ years have a richer knowledge of marine resources than younger fishers (men and women), measured by the number of unique species they could identify or describe. Our ethnography findings, highlight the importance of maintaining this endangered Indigenous knowledge to preserve marine resources of significance for future generations.